Language And Revolution: A Linguistic Analysis Of Manipulation In George Orwell's Works - Abdul-latif Emad (université msila, 2022)
This article tackles how language fails revolutions. It studies the linguistic techniques of manipulation that have been in Orwell’s ‘Animal Farm’ to control the community aftermath of a revolution. The article extends its discussion of political manipulation to include Orwell’s vivid article ‘Politics and English Language’. This article purchases the study of Orwell’s critique of political language via introducing an in-depth linguistic analysis of mass manipulation, as it was practiced in allegorical worlds
Keywords: Language and politics ; George Orwell ; revolution ; manipulation ; Animal Farm